2017
DOI: 10.1158/1078-0432.ccr-16-0970
|View full text |Cite
|
Sign up to set email alerts
|

TNFα-Induced Mucin 4 Expression Elicits Trastuzumab Resistance in HER2-Positive Breast Cancer

Abstract: We identified TNFα-induced MUC4 expression as a novel trastuzumab resistance mechanism. We propose MUC4 expression as a predictive biomarker of trastuzumab efficacy and a guide to combination therapy of TNFα-blocking antibodies with trastuzumab. Clin Cancer Res; 23(3); 636-48. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 43 publications
6
93
2
Order By: Relevance
“…13B). Consistent with cell line-based studies reported in the literature [30][31][32][33] trastuzumab induced tumor regression in mucin negative WHIM8 but not in mucin positive WHIM35 (Fig. 5f).…”
Section: Articlesupporting
confidence: 91%
“…13B). Consistent with cell line-based studies reported in the literature [30][31][32][33] trastuzumab induced tumor regression in mucin negative WHIM8 but not in mucin positive WHIM35 (Fig. 5f).…”
Section: Articlesupporting
confidence: 91%
“…Interestingly, WHIM35 has high expression of mucin proteins compared to WHIM8 (Supplementary Figure 13A) indicating this case was a phenocopy of BCN1369 (Supplementary Figure 13B). Consistent with cell line-based studies reported in the literature [30][31][32][33] that proposed that mucin expression might inhibit trastuzumab-mediated response, trastuzumab induced tumor regression in WHIM8 but not in WHIM35 ( Figure 5F). Drawing from the observation that BCN1369 also exhibited elevated PI3K-Akt-mTOR signaling ( Figure 5B), together with a recent report that showed mTOR mediated MUC1 induction in multiple breast cancer cell lines 30 , these PDX models were additionally treated with the small molecule mTOR inhibitor everolimus.…”
Section: Proteomics and Phosphoproteomic Analyses Of Acute On-treatmesupporting
confidence: 90%
“…Recently it was shown that TNFα can induce MUC4 expression in HER2-positive breast and gastric cancer cells (38). Moreover, they observed a strong association between MUC4-positive tumors and a shorter DFS in patients receiving adjuvant trastuzumab-based treatment (39). We show here that [ 131 I]-2Rs15d binds four times higher to JIMT-1 compared to [ 131 I]-trastuzumab, while binding to trastuzumab-responsive BT474/M1 was similar for both compounds (Fig.…”
Section: Discussionmentioning
confidence: 99%